The Influence of Islamic leadership on Employee Psychological Well-Being with the Mediation of Organizational Justice - Immanuel Mu'ammal; Achmad Mohyi (Pustaka Peradaban, 2024)
This study explores the relationship between Islamic leadership, organizational justice, and employee psychological well-being in the workplace. Islamic leadership, rooted in the teachings of Islam, is examined for its influence on employee well-being. The concept of psychological well-being, encompassing self-acceptance, positive relationships, autonomy, environmental mastery, purpose in life, and personal growth, is the primary focus of this research. A quantitative research method with a positivist approach and survey methodology was employed. The results reveal a significant relationship between Islamic leadership, organizational justice, and employee well-being. Organizational justice is also found to mediate the relationship between Islamic leadership and psychological well-being. These findings hold significant implications for organizational management, emphasizing the importance of religious values in leadership and justice in creating a fair work environment. Islamic leadership can serve as a source of motivation for employees, while organizational justice can enhance employee well-being. The study's findings can be utilized as a foundation for developing more effective management strategies to improve employee psychological well-being in the workplace. This research contributes significantly to understanding the relationship between Islamic leadership, organizational justice, and employee well-being